Cartilage regeneration - Lin, Yunfeng (Humana Press, 2017)
This book focuses on cartilage defects and new mesenchymal stem cell-based treatments for their repair and regeneration. Early chapters provide a review of current etiological findings and repair methods of cartilage defects. The next chapters discuss fundamental concepts and features of MSCs, including their proliferation, differentiation, migration and immunomodulatory effects. The discussion also includes clinical applications of MSCs in cartilage tissues, especially with regards to various animal models, biomaterials and transferring techniques. Cartilage Regeneration focuses on the biology of MSCs and their possible applications in cartilage reconstruction, with the goal of bringing new insights into regenerative medicine. It will be essential reading for researchers and clinicians in stem cells, regenerative medicine, biomedical engineering and orthopedic surgery.
Includes index.
Keywords: Cartilage -- Regeneration.; Tissue scaffolds.; elektronické knihy; electronic books